MECHANISM OF ALUMINUM TOXICITY AVOIDANCE IN TROPICAL RICE (Oryza sativa), MAIZE (Zea mays), AND SOYBEAN (Glycine max) - D. Nursyamsi; M. Osaki; T. Tadano (Indonesian Journal of Agricultural Science, 2002)
Planting Al tolerant crops is an economically justifiable approach in crop production on acid soils. Experiments were conducted to study the mechanisms of Al tolerance among species and varieties of tropical rice, maize, and soybean with previously known levels of Al tolerance. These varieties were hydroponically cultured in 0, 5, 10, and 30 mg l-1 Al with complete nutrient solution at pH 4. The results show that root/shoot ratio of dry weight at 10 mg l-1 Al treatment was an important parameter to indicate differential Al tolerance in maize. Oxalic acid exudation from roots cannot always explain the Al tolerance. Total organic acid concentration in roots at 10 mg l-1 Al treatment indicated a difference of Al tolerance in soybean and lowland rice. Aluminum translocation from roots to shoots was lower in  tolerant varieties than in sensitive varieties of soybean. Increased Al concentration in shoots with increased Al level in the solution was larger in soybean and maize than in lowland or upland rice. Among varieties of  soybean, the Al concentration in shoots increased drastically in Wilis (Al-sensitive variety) with increase Al level, while in Kitamusume (Al-tolerant variety) it did not.